Generalized Mittag-Leffler Type Function: Fractional Integrations and Application to Fractional Kinetic Equations - Nisar, Kottakkaran Sooppy (Frontiers in Physics, 2020)
The generalized fractional integrations of the generalized Mittag-Leffler type function (GMLTF) are established in this paper. The results derived in this paper generalize many results available in the literature and are capable of generating several applications in the theory of special functions. The solutions of a generalized fractional kinetic equation using the Sumudu transform is also derived and studied as an application of the GMLTF.